On removing showers from the IAU Working List of Meteor Showers. (March 2020) - Jenniskens, Peter; Jopek, Tadeusz J.; Janches, Diego; Hajduková, Maria; Kokhirova, Gulchehra I.; Rudawska, Regina
Abstract: The purpose of the IAU Working List of Meteor Showers is to keep the literature transparent by assigning a unique name, number and three-letter code to each newly reported meteor shower. Here, a report is given on newly adopted procedures for the removal of showers from the Working List. Entries that are shown to be duplicates or statistically insignificant detections in published papers can be moved to the List of Removed Showers, with the reason for removal described. In order to help identify duplicates, a link to a "look-up table" that describes the dispersion of a shower's solar longitude, radiant and speed, will be added to the shower entries. Highlights: A report is given on newly adopted procedures to maintain the IAU Working List of Meteor Showers and on how to submit new meteor shower detections.